Expanding Your Raspberry Pi Storage, printing, peripherals, and network connections for your Raspberry Pi - Soper, Mark Edward (Apress, 2017)
Gain a deeper understanding of how Raspberry Pi works to get the results you want right in the palm of your hand. This book helps you understand the right connections and software to drive your Raspberry Pi into opening the worlds of programming, electronic experiments, system control, digital imaging, and the Internet of Things to you. You'll discover how to expand your Pi's storage for bigger programs, use its onboard connections to interface with cameras and control devices, printers and scanners. You'll also see how to share information with Windows and Apple computers and mobile devices, and use it away from AC power. You'll be able to turn any HDTV into a media player; stream and share files from desktop and mobile devices; use your Pi for image capture via camera or scanner; and more! Expanding Your Raspberry Pi is your guide to doing almost anything a bigger computer can do - if you're ready for the challenge.
Includes bibliographical references
Keywords: Computer science; Microprogramming; Computer input-output equipment; Computer programming; Electronic Data Processing; Informatique; Microprogrammation; Ordinateurs; Équipement d'entrée-sortie; Programmation (Informatique); computer programming; Computer networking & communications; Computer programming; software development; Computer hardware; Algorithms & data structures; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference